2011
DOI: 10.4038/jccpsl.v14i1.2944
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Betel Chewing Among Males in Colombo and Polonnaruwa Districts

Abstract: ObjectivesTo assess the prevalence of betel chewing among adult males in a rural and urban district in Sri Lanka and describe the demographic characteristics of betel chewers. MethodsBetel use among 2684 males aged >18 years resident in a rural (Polonnaruwa) and urban (Colombo) district in Sri Lanka was assessed using multistage cluster sampling. Data on quantity and frequency of use was obtained using an interviewer administered questionnaire. ResultsPrevalence of betel chewing was 17.6% in the rural and 1.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Epidemiological studies have shown that betel quid chewing is a major risk factor for development of both oral and pharyngeal cancers and also oral pre-cancerous lesions [ 2 , 4 ]. Earlier reports in the 1980s from Sri Lanka and a recent report from Solomon Islands [ 8 , 9 ] shows a very high rate of approximately 50 % betel quid chewers in both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies have shown that betel quid chewing is a major risk factor for development of both oral and pharyngeal cancers and also oral pre-cancerous lesions [ 2 , 4 ]. Earlier reports in the 1980s from Sri Lanka and a recent report from Solomon Islands [ 8 , 9 ] shows a very high rate of approximately 50 % betel quid chewers in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports in the 1980s from Sri Lanka and a recent report from Solomon Islands [ 8 , 9 ] shows a very high rate of approximately 50 % betel quid chewers in both sexes. However, a recent report from Sri Lanka [ 4 ] indicates a reduction in numbers of betel chewers, most probably the result of life style changes that have occurred over the years. In addition, a remarkable decline in the habit of smoking is also observed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low affordability is supported by the fact that 10.1% of males used smokeless tobacco in the form of betel quid, which is cheaper than cigarettes. This is much higher than the prevalence of 1.7% reported among the general population in urban areas [37]. Betel quid contains betel leaf (Piper betle), arecanut (Areca catechu) slaked lime (calcium hydroxide) and tobacco [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the rural areas, prevalence of betel chewing was significantly associated with age, and the odds of being a betel quid chewer increased with age; with the odds for those aged >65 years being 19.85 compared to the reference group 18-24 years [ Table 2]. [8] Asian betel-quid consortium of South and East Asia carried out the prevalence study on betel quid chewing across six Asian countries. In Sri Lanka, the study among 1,072 subjects from three provinces of Gangawata Korale, Udunuwara, and Yatinuwara with the response rate of 99%, showed the prevalence of betel quid with tobacco was 6.4% among men and 3.2% among women.…”
Section: Smokeless Tobacco Use Among Adultsmentioning
confidence: 99%